Methods of Weaning From Mechanical Ventilation in Adult: A Network Meta-Analysis - Jhou, Hong-Jie; Chen, Po-Huang; Ou-Yang, Liang-Jun; Lin, Chin; Tang, Shih-En; Lee, Cho-Hao (Frontiers in Medicine, 2021)
Background/Objective: The aim of study is to assess the efficacy of each ventilator weaning method for ventilated patients in intensive care units (ICUs). Methods: A systematic search was conducted using PubMed, Embase, and China National Knowledge Infrastructure to identify randomized control studies on ventilated patients regarding extubation associated outcomes (weaning success or failure, proportion requiring re-intubation, or mortality) from inception until April 01, 2020. Commonly used ventilation modes involved pressure support ventilation, synchronized intermittent mandatory ventilation, automatic tube compensation, continuous positive airway pressure, adaptive support ventilation, neurally adjusted ventilatory assist, proportional assisted ventilation, and SmartCare. Pooled estimates regarding extubation associated outcomes were calculated using network meta-analysis. Results: Thirty-nine randomized controlled trials including 5,953 patients met inclusion criteria. SmartCare and proportional assist ventilation were found to be effective methods in increasing weaning success (odds ratio, 2.72, 95% confidence interval (CI), 1.33-5.58, P-score: 0.84; odds ratio, 2.56, 95% CI, 1.60-4.11, P-score: 0.83; respectively). Besides, proportional assist ventilation had superior in reducing proportion requiring re-intubation rate (odds ratio, 0.48, 95% CI, 0.25-0.92, P-score: 0.89) and mortality (odds ratio, 0.48, 95% CI, 0.26-0.92, P-score: 0.91) than others. Conclusion: In general consideration, our study provided evidence that weaning with proportional assist ventilation has a high probability of being the most effective ventilation mode for patients with mechanical ventilation regarding a higher rate of weaning success, a lower proportion requiring reintubation, and a lower mortality rate than other ventilation modes.